A variant of Takotsubo syndrome concomitant with left atrial myxoma. Issue 3 (3rd March 2022) - Ishibashi, Naoki; Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Oda, Noboru; Tachibana, Hitoshi; Katayama, Akira
Abstract: We treated an 80‐year‐old Japanese woman who had Takotsubo syndrome (TTS) concomitant with a left atrial (LA) tumor. Left ventriculography revealed a variant of TTS. In cardiac surgery, the LA mass was successfully resected without embolism, with the pathological diagnosis of myxoma. Abstract : It is important to prevent embolic events in cardiac myxoma patients. Takotsubo syndrome (TTS) due to cardiac myxomas is potentially underdiagnosed. Heart failure symptoms might signify TTS concomitant with cardiac myxoma.